2003
DOI: 10.1002/bit.10596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of operating variables on the expanded bed adsorption of Saccharomyces cerevisiae cells using a concanavalin A derivatized perfluorocarbon

Abstract: The use of fluidizable affinity adsorbents for the adsorption of cells in expanded mode is investigated. Affinity adsorbents have been synthesized by immobilizing the lectin Concanavalin A onto the surface of triazine-activated perfluorocarbon-solids. The adsorbents were found to adsorb Saccharomyces cerevisiae cells from solution with adsorption capacities of up to 6.8 x 10(9) cells mL(-1). Adsorption kinetics were rapid with a time constant of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The phenomenon indicates that S. cerevisiae is captured by the Con A interface. The experimental result is agreed with previous literature reports [21,22].…”
Section: Bacteria Adhesionsupporting
confidence: 95%
“…The phenomenon indicates that S. cerevisiae is captured by the Con A interface. The experimental result is agreed with previous literature reports [21,22].…”
Section: Bacteria Adhesionsupporting
confidence: 95%
“…Many research studies have employed conA for lectin affinity chromatography. Of special interest to the authors, Clemmitt and Chase investigated the roles of operating variables and established optimal parameters for designing expanded bed columns for high capacity and high efficiency capture of specific glycosylated cells. Reichelt et al describe efforts to improve the throughput of lectin affinity chromatographic media, including the development of monolithic spin‐type columns that employ conA for enriching and purifying glycan mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The expanded bed, already known for its ability to segregate particles based on size, and its various applications in adsorption, as reported by Chase and Draeger (1992), Chang and Chase (1996), Chen et al (2003), Clemmitt and Chase (2003), Lin et al (2003), Ujam et al (2003), and Abdullah and Chase (2005), is demonstrated in this paper to have a novel application in the separation and enrichment of neural stem cells.…”
Section: Introductionmentioning
confidence: 81%